STRESS UTILISATION OF JACKET STRUCTURE UNDER ENVIRONMENTAL LOADING (Jurnal Mekanikal, 2018)
The level of stress utilisa tion within structural elements due toexternal and transf erred loads between structural members may beestimated. This may routinely be performed at early design stageswhere all loading parameters and assumptions are p redicted to act onthe structure that results the response under normal operatingcondition. 771e paper addresses loading parameters. discuss analysissteps that have been applied to the structure and illustrate subsequentresults ofthe stress utilisation within the structure due to the responseto external and transf erred load acting on the structure. Particularapplication includes the studies on typical shallows or medium waterdepth jacket structures under normal and extreme loading conditions.
Keywords: Keywords